Complainers versus non-complainers retaliatory responses towards service dissatisfactions - Phau, Ian; Baird, Michael (Emerald Group Publishing Limited, 2008)
The paper aims to investigate the different forms of retaliatory responses towards dissatisfactory service encounters experienced by Australian consumers. It further compares demographic and psychographic profiles of complainers versus non-complainers. 1200 mail surveys were sent out through a random list of addresses obtained from the White Pages. Data from 237 usable surveys (29.1%) were analysed using a series of statistical techniques including factor analysis to profile psychographic factors and discriminant analysis to identify complainers from non-complainers. It is found that both complainers and non-complainers engage in some form of retaliatory responses. Complainers have a high sense of justice, are less conservative and have a more positive attitude towards complaining than their non-complaining counterparts. Gender, income and education have no effect on complaining behaviour for both complainers and non-complainers.The high number of retaliation through 'exit' is a concern for Australian firms. Firms have to make an effort to identify the conditions exactly how each occurs and the strategies best available to rectify them. Mechanisms can be put in place to reduce these occurrences to improve the business as a whole. The paper matches the demographic and psychographic profiles of complainers and non-complainers with potential types of products and services and the related retaliatory responses.